The crisis of democracy: Schmitt‘s critique of liberal democracy - Petrović, Luka (Sociološki pregled, 2022)
Based on Schmitt‘s critique of parliamentary democracy during the interwar crisis period, this paper answers the question of how relevant his insights are today regarding the political consequences of ignoring power relations in a society, and what negative effects are produced by depoliticization of economic and social relations. The author argues that Schmitt accurately diagnoses the key problems of parliamentary democracies. These are their inability to protect themselves from powerful social groups that displace decision-making from parliament, and neutrality towards political content potentially leading to the abuse of political institutions. However, solutions should not be sought in his work, especially because of the willingness to accept the broad competencies of the executive power in times of crisis and justify the suppression of party pluralism.
Keywords: Carl Schmitt; parliamentarism; democracy; crisis; liberal state